The forms of destructive behavior in the workplace - D A Narozhnaia (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
Personnel have become a key resource of organizations in the contemporary society for the way personnel fulfills its work functions can provide important advantages in the competitive market. However, despite the fact that organizations’ management pays great attention to the development of the constructive forms of work behavior, various forms of destructive behavior in the workplace are quite widespread nowadays. The author uses the concept “destructive labor behavior” to denote such observable actions of employees that hinder achieving organizations’ aims and entail negative consequences. The article analyzes relationships between concepts “destructive labor behavior”, “social behavior” and “organizational behavior”; identifies the most common types of destructive labor behavior, such as absenteeism, theft, sabotage, lowered labor activity, and their key features; considers their negative consequences, such as decreased production, decline in the quality of products or services, conflicts in the team, tensions between workers and employers; analyzes different classifications of the destructive forms of labor behavior. The author concludes that we need a general classification of the destructive forms of labor behavior based on their grouping on three grounds: the essence of the negative consequences of the destructive behavior; the violated legal norms; the causes of the destructive behavior. Moreover, the article identifies three groups of organizational factors that can generate destructive forms of labor behavior - production factors (content, organization and conditions of work), social factors (group relations) and psychological (personal characteristics of employees) - and provides recommendations to reduce their impact on the organization.